Effects of inoculation of Lactiplantibacillus plantarum and Lentilactobacillus buchneri on fermentation quality, aerobic stability, and microbial community dynamics of wilted Leymus chinensis silage - Wu, Baiyila; Hu, Zongfu; Wei, Manlin; Yong, Mei; Niu, Huaxin (Frontiers in Microbiology, 2022)
Leymus chinensis is an important crop that can be fed to ruminants. The purpose of this study was to investigate the roles of Lactiplantibacillus plantarum and Lentilactobacillus buchneri in fermentation quality, aerobic stability, and dynamics of of wilted Leymus chinensis silage microorganisms. Wilted Leymus chinensis silages were ensiled with/without L. plantarum and L. buchneri. After 14 and 56 days of ensiling, the silos were opened and subjected to a 7-day aerobic deterioration test. This study looked at the composition of fermentation products as well as the microbial communities in silage. Silage inoculated with L. plantarum and L. buchneri had an increased lactic acid content as well as lactic acid bacterial quantity, but a decrease in pH, butyric acid, 2,3-butanediol, and ethanol levels was seen during ensiling. Non-treated and L. plantarum-treated silages deteriorated in the 7-day spoilage test after opening day 14 silos, whereas L. buchneri-inoculated silage showed no signs of deterioration. Lactobacillus abundance increased in the 7-day spoilage test after opening day 56 silos, while undesirable microorganisms such as Acetobacter, Bacillus, and molds such as Aspergillus, Penicillium were inhibited within L. plantarum- and L. buchneri-inoculated silages. The composition of fermentation products was related to the bacterial community, particularly Lactobacillus, Enterococcus, and Acetobacter. To summarize, L. plantarum and L. buchneri-inoculated silage enhanced fermentation quality during ensiling and inhibited aerobic spoilage in a 7-day spoilage test of 56 days ensiling within wilted Leymus chinensis silage..